2018
DOI: 10.1038/s41437-018-0152-4
|View full text |Cite|
|
Sign up to set email alerts
|

Development of G: a test in an amphibious fish

Abstract: Heritable variation in, and genetic correlations among, traits determine the response of multivariate phenotypes to natural selection. However, as traits develop over ontogeny, patterns of genetic (co)variation and integration captured by the G matrix may also change. Despite this, few studies have investigated how genetic parameters underpinning multivariate phenotypes change as animals pass through major life history stages. Here, using a self-fertilizing hermaphroditic fish species, mangrove rivulus (Krypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 98 publications
1
7
0
Order By: Relevance
“…Genetic variance for life history and fitness traits is often low (e.g., McFarlane et al 2014), and often 505 decreases with ontogeny (e.g., Aguirre et al 2014). In contrast, our results suggested increases in genetic 506 variance with development, which has been found previously in laboratory conditions (Styga et al 2018). 507…”
supporting
confidence: 54%
“…Genetic variance for life history and fitness traits is often low (e.g., McFarlane et al 2014), and often 505 decreases with ontogeny (e.g., Aguirre et al 2014). In contrast, our results suggested increases in genetic 506 variance with development, which has been found previously in laboratory conditions (Styga et al 2018). 507…”
supporting
confidence: 54%
“…2018; Styga et al. 2019). To calculate phenotypic correlations, we extracted fitted means for each variable and calculated Pearson's correlation coefficients using the car package, with sequential Bonferroni corrections to account for compounding Type I error.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Cheverud's conjecture has shown that well estimated G‐matrices tend to resemble P‐matrices (Cheverud, 1988), especially for morphological traits with generally high heritabilities (i.e., high contribution of genetic factors to overall variance), which is the case for lizard limb traits. Moreover, empirical examples of similarity between G and P are mounting in the literature (e.g., Marroig & Cheverud, 2001; Phillips & Arnold, 1999; Roff, 1996; Sodini et al, 2019; Styga et al, 2019). Finally, we compared A. scriptus P‐matrices with a G‐matrix of the closest relative, A. cristatellus , extracted from McGlothlin et al (2018), and matrices are substantially similar (see Supporting Information, Tables S2 and S3).…”
Section: Methodsmentioning
confidence: 99%